1976
DOI: 10.1159/000240848
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Litter Size on the Growth, Survival and Behaviour of Neonatal Bulbectomised Mice

Abstract: Bilateral lesions of the olfactory bulbs in 1-day-old mice led to a slow rate of growth both before and after weaning and the growth changes were positively associated with the size of the lesion. Mothers continued to care for the bulbectomised mice which showed no evidence of retarded motor development though their eyes opened later and they were less active when exposed to an artificial perfume. Bulbectomised mice failed to survive in litters of two where both infants were bulbectomised and in litters with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1976
1976
2006
2006

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Consistent with this hypothesis, in the oVspring of null £ heterozygous matings, the ratio of heterozygous to null oVspring does not deviate from the expected Mendelian ratio of 50% heterozygous to 50% null (N=46, P=0.77). The increased survival of null pups in these litters may be attributable to less competition from non-null littermates; however, the presence of the heterozygous littermates is important in stimulating lactation in the mother (Cooper and Cowley 1976). We have also observed that in two litters born to a null £ null mating pair, no pups survived past two days of age.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Consistent with this hypothesis, in the oVspring of null £ heterozygous matings, the ratio of heterozygous to null oVspring does not deviate from the expected Mendelian ratio of 50% heterozygous to 50% null (N=46, P=0.77). The increased survival of null pups in these litters may be attributable to less competition from non-null littermates; however, the presence of the heterozygous littermates is important in stimulating lactation in the mother (Cooper and Cowley 1976). We have also observed that in two litters born to a null £ null mating pair, no pups survived past two days of age.…”
Section: Discussionmentioning
confidence: 58%
“…Direct observations did not indicate gross heart defects as a cause of perinatal lethality in the null animals. Because null mice have been determined to have anosmia, the failure to thrive is potentially a consequence of the inability of the pups to respond to olfactory cues from their mother, especially in litters from heterozygous mating pairs where competition is more intense for the null pups, as only 25% of the pups are expected to be of this genotype (Cooper and Cowley 1976;Hongo et al 2000;Teicher et al 1978). The null pups likely have more diYculty nipple-searching and suckling, as daily weight gain is a reliable indicator of successful suckling (Coppola et al 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They ran the maze rapidly, paused at tire centre only briefly and seldom failed to run the maze in the time allowed. Their behaviour, while typical of that o f parent generation under nourished rats (10), was radically different from the bulbectomised mice and suggests that the slow growth consequent upon the restric tion of food intake in the one instance and tire impairment o f suckling that accompanies neonatal bulbectomy on the other are not expressed in the behaviour o f adult animals in the same way (see also 4,5,8,9). The mice with a history o f undernourishment actively explored the goal box and attempted to re enter the maze, behaviour that was less obvious in the other samples.…”
Section: Discussionmentioning
confidence: 99%
“…The placement of lesions in the olfactory bulbs o f neonatal rats and mice also leads to a retardation of growth, and sexual maturation is delayed (4,5,8). The factors responsible for the failure of normal growth relate both to the slowness of the animals to reach and attach themselves to the mother's nipple and to changes in feeding which in turn no doubt aggravate the difficulties in obtaining adequate food supplies.…”
Section: Discussionmentioning
confidence: 99%